2018
DOI: 10.32598/ptj.8.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Balance During Gait in Children With Spastic Diplegic Cerebral Palsy Versus Normal Children

Abstract: Purpose: Cerebral Palsy (CP) can negatively affect dynamic stability in children with spastic diplegic Cerebral Palsy during walking. This condition results in a high risk of falling. There is limited evidence regarding the dynamic stability of children with Cerebral Palsy. Thus, this study aimed to investigate the dynamic stability of children with spastic diplegic Cerebral Palsy, compared to typically developed children during walking. Methods: Sixteen children including 8 with spastic diplegic Cerebral Pals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…However, in most of the studies the stability was evaluated by berg balance scale (15). In the recent research the effect of balance training by Biodex on stability of CP was evaluated (16,17). It has been shown that Biodex training is a useful tool to improve stability in this group of subjects (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…However, in most of the studies the stability was evaluated by berg balance scale (15). In the recent research the effect of balance training by Biodex on stability of CP was evaluated (16,17). It has been shown that Biodex training is a useful tool to improve stability in this group of subjects (18,19).…”
Section: Introductionmentioning
confidence: 99%